Anti-acetic acid additive for conductive silver paste of solar cell and preparation method of anti-acetic acid additive
By adding specific composition anti-acetic acid additives to the conductive silver paste, the problem of efficiency attenuation of solar cells in the acetic acid environment is solved, and the reduction of acetic acid attenuation and the maintenance of initial efficiency is achieved.
Patent Information
- Application Number
- CN202311230101.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-22
- Publication Date
- 2025-03-28
AI Technical Summary
The current solar cells have a large efficiency attenuation in the acetic acid environment, and it is difficult to maintain the initial efficiency while reducing the acetic acid attenuation.
In the preparation process of conductive silver paste, an anti-acetic acid additive is added, which consists of Te2O3, B2O3, PbO, Bi2O3 and Nb2O3. By adjusting the proportion and particle size of each component, its anti-acetic acid performance is improved.
The acetic acid attenuation of the solar cell is significantly reduced, while maintaining the initial efficiency of the solar cell, without significantly changing the formulation and preparation method of the conductive silver paste.
Smart Images

Figure BDA0004463589770000181 
Figure BDA0004463589770000191
Abstract
Description
Technical Field
[0001] The invention relates to an acetic acid resistant additive, a conductive silver paste for preparing a solar cell comprising the acetic acid resistant additive, and a solar cell prepared from the conductive silver paste.
[0002] The present invention further relates to the use of the above-mentioned acetic acid resistance additive in enhancing the acetic acid resistance of solar cells. Background Art
[0003] Solar cells are devices that convert light energy from the sun into electrical energy. Light shines on the silicon wafer of the substrate, generating electrons and holes, which are guided through electrodes located on the front side (i.e. the side illuminated by light) and the back side (i.e. the side not illuminated by light) of the substrate, thus forming a current to obtain electrical energy.
[0004] The electrode in contact with the silicon wafer on the front side of the substrate of the prior art solar cell is usually manufactured by applying a conductive silver paste to the substrate by screen printing and then sintering the conductive silver paste. The conductive silver paste contains silver powder, glass powder, an organic carrier and additives. The glass powder used for the conductive silver paste is usually a glass powder of a high-lead system. The glass powder is used to open the passivation film on the silicon wafer so that the silver in the conductive silver paste forms contact with the silicon under the passivation layer after sintering.
[0005] The substrate with electrodes is encapsulated with EVA (ethylene-vinyl acetate) to become a photovoltaic module of a solar cell. The acetic acid produced by the EVA film when it comes into contact with water vapor easily reacts with lead oxide and silver, resulting in poor weather resistance of the module and a significant reduction in efficiency. However, while reducing the amount of lead, the acetic acid-resistant conductive silver paste will increase the corrosion of the glass on the silicon substrate, resulting in a loss of open circuit voltage and efficiency.
[0006] After the solar cell sheets of the prior art are soaked in acetic acid, the initial efficiency attenuation (hereinafter referred to as acetic acid attenuation) is more than 5%. There is no balance between the initial efficiency and the acetic acid resistance of the cell sheets.
[0007] Therefore, in the prior art, acetic acid attenuation is mostly reduced by changing the slurry formula, which requires a significant change in the slurry formula and has a great impact on the efficiency of the cell.
[0008] Therefore, there is an urgent need in the art for a simple method for reducing acetic acid attenuation. Summary of the invention
[0009] The inventors found that by adding an acetic acid-resistant additive during the preparation of the conductive silver paste, the acetic acid attenuation of the solar cell can be significantly reduced.
[0010] Specifically, the present invention includes the following contents:
[0011] The present invention relates to an acetic acid resistant additive, wherein based on the total weight of the acetic acid resistant additive, the acetic acid resistant additive comprises:
[0012] Te2O3: 20-80 wt%, preferably 40-70 wt%, more preferably 45-60 wt%, most preferably 45-55 wt%;
[0013] B2O3: 0-10 wt%, preferably 0-8 wt%, more preferably 2-6 wt%, most preferably 3-5 wt%;
[0014] PbO: 1-70 wt %, preferably 5-60 wt %, more preferably 20-50 wt %, most preferably 25-50 wt %;
[0015] Bi2O3: 5-50 wt%, preferably 10-40 wt%, more preferably 10-30 wt%, most preferably 10-25 wt%; and
[0016] Nb2O3: 0-20 wt%, preferably 0-10 wt%, more preferably 2-6 wt%, most preferably 3-5 wt%;
[0017] The total amount of each component is 100% by weight.
[0018] The acetic acid resistant additive of the present invention preferably has a particle size D50 of 0.1-5 μm, preferably 1-2 μm, and / or 1-5 μm 2 / g, preferably 1.5-3.5m 2 / g specific surface area.
[0019] The present invention also relates to a conductive silver paste, which comprises silver powder, glass powder, an organic carrier and an optional conductive silver paste additive, and the acetic acid resistant additive of the present invention.
[0020] The conductive silver paste of the present invention comprises, based on the total weight of the conductive silver paste:
[0021] Silver powder: 80-94 wt %, preferably 79-93 wt %, more preferably 82-92 wt %;
[0022] Glass powder and acetic acid resistant additive: 2-15% by weight, preferably 2.5-8% by weight, more preferably 0.1-6% by weight, wherein the weight ratio of glass powder to acetic acid resistant additive is 1:1-20:1, preferably 5:1-15:1, more preferably 8:1-12:1;
[0023] Organic carrier: 2-20 wt %, preferably 3-15 wt %, more preferably 5-10 wt %;
[0024] The total amount of each component is 100% by weight.
[0025] In the conductive silver paste of the present invention, based on the total weight of each component of the glass powder, the glass powder comprises:
[0026] Tellurium oxide: 10-50 mol%, preferably 15-40 mol%;
[0027] Lead oxide: 10-30 mol%, preferably 15-25 mol%;
[0028] Bismuth oxide: 0-15 mol%, preferably 5-10 mol%;
[0029] Silicon dioxide: 0-30 mol%, preferably 5-25 mol%;
[0030] Preferably an oxide of an alkali metal selected from Li, Na, K or a combination thereof: 0-30 mol%, preferably 15-25 mol%;
[0031] Preferably an oxide of an alkaline earth metal selected from Ca, Mg, Sr or a combination thereof: 0-10 mol %, preferably 0-5 mol %; and
[0032] Oxides of transition metals preferably selected from Zn, Cu, Mo, W, Ag, V, Cr, Mn, Co, Ni, Nb, Ta, Th, Ge, La, Sb, Ce, Al or combinations thereof: 0-40 mol%, preferably 5-25 mol%;
[0033] The sum of the contents of each component is 100 mol%.
[0034] The present invention also relates to a solar cell comprising an electrode obtained from the conductive silver paste of the present invention.
[0035] In the solar cell of the present invention, the electrode is located on a P-type or N-type silicon wafer with a passivation layer, preferably on a P-type silicon wafer with a passivation layer.
[0036] The present invention also relates to the use of the acetic acid resistant additive of the present invention, which is used to reduce the acetic acid attenuation of solar cell sheets while maintaining the initial efficiency of the solar cell sheets, wherein the acetic acid resistant additive of the present invention or the acetic acid resistant additive of the present invention is added to the conductive silver paste used to prepare the solar cell sheets.
[0037] The present invention also relates to a method for reducing acetic acid attenuation of solar cell sheets while maintaining the initial efficiency of the solar cell sheets, wherein the acetic acid resistant additive of the present invention is added to the conductive silver paste used to prepare the solar cell sheets before sintering the conductive silver paste.
[0038] In this article, "about" for modifying numerical values means that the numerical value should take into account experimental errors and changes that can be expected by those skilled in the art. In particular, "about" refers to a numerical value within the range of plus or minus 20%, preferably 10%, and more preferably 5% of the modified numerical value. Specific implementation plan
[0039] Anti-acetic acid additives
[0040] The invention relates to an acetic acid resistant additive and a preparation method thereof. The acetic acid resistant additive can be used to prepare conductive silver paste used in solar cells.
[0041] The acetic acid resistant additive of the present invention comprises, based on its total weight:
[0042] Tellurium oxide (Te2O3): 20-80 wt%, preferably 40-70 wt%, more preferably 45-60 wt%, most preferably 45-55 wt%;
[0043] Boron oxide (B2O3): 0-10 wt%, preferably 0-8 wt%, more preferably 2-6 wt%, most preferably 3-5 wt%;
[0044] Lead oxide (PbO): 1-70 wt %, preferably 5-60 wt %, more preferably 20-50 wt %, most preferably 25-50 wt %;
[0045] Bismuth oxide (Bi2O3): 5-50 wt%, preferably 10-40 wt%, more preferably 10-30 wt%, most preferably 10-25 wt%; and
[0046] Niobium oxide (Nb2O3): 0-20 wt%, preferably 0-10 wt%, more preferably 2-6 wt%, most preferably 3-5 wt%;
[0047] The total amount of each component is 100% by weight.
[0048] In one embodiment of the present invention, the acetic acid resistant additive of the present invention is prepared by the following method: uniformly mixing the components of the acetic acid resistant additive, melting the mixture to obtain glass, preferably quenching in deionized water, and finally preparing particles with a desired particle size.
[0049] Preferably, the acetic acid-resistant additive of the present invention is prepared by the following method: the components of the acetic acid-resistant additive of the present invention are mixed uniformly, the mixture is loaded into a crucible, the crucible is placed in a muffle furnace and the mixture is melted at a high temperature, then the molten glass is removed from the muffle furnace and poured into a bucket filled with deionized water for water quenching, and the quenched glass slag is ground with a ball mill to obtain a powder with a desired particle size D50.
[0050] In the above method, the temperature of the muffle furnace is high enough to melt the components of the acetic acid resistant additive of the present invention, and the melting time is long enough to uniformly mix the components.
[0051] More preferably, in the preparation of the acetic acid resistant additive of the present invention, the temperature of the muffle furnace is 800-1500° C., preferably 900-1200° C., and the melting time of the mixture is 15 minutes to 2 hours, preferably 30 minutes to 1 hour.
[0052] The acetic acid resistant additive of the present invention preferably has a specific particle size and specific surface area.
[0053] Particle size is a particle property known to those skilled in the art. Particle size D50 is the median particle size or median value of the particle size distribution, which is the particle size value at the 50% position in the cumulative distribution. Particle size D50 and its distribution can be measured via laser diffraction, dynamic light scattering, imaging, electrophoretic light scattering, or any other method known in the art.
[0054] In one embodiment of the present invention, the acetic acid resistant additive of the present invention has a particle size D50 of 0.1-5 μm, for example 0.2 μm, 0.5 μm, 0.8 μm, 1 μm, 1.2 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm or 4.5 μm, preferably 1-2 μm.
[0055] In one embodiment of the present invention, the acetic acid resistant additive of the present invention has 1-5m 2 / g, preferably 1.5-3.5m 2 / g specific surface area.
[0056] Conductive silver paste
[0057] The present invention further relates to a conductive silver paste comprising the acetic acid resistant additive of the present invention and a preparation method thereof.
[0058] The present invention comprises the step of adding the acetic acid resistant additive of the present invention into the conductive silver paste conventionally used in the art.
[0059] In one embodiment of the present invention, the conductive silver paste comprises silver powder, glass powder, an organic vehicle, and a conductive silver paste additive.
[0060] In one embodiment of the present invention, the conductive silver paste of the present invention comprises silver powder which is commonly used in the art to prepare conductive silver paste for solar cells.
[0061] In one embodiment of the present invention, the conductive silver paste may contain 80-94 wt %, preferably 79-93 wt %, more preferably 82-92 wt % of silver powder, based on the total weight of the conductive silver paste.
[0062] In one embodiment of the present invention, the particle size D50 of the silver powder may be 0.1-3 μm, preferably 0.1-1.5 μm or 0.1-1 μm.
[0063] In one embodiment of the present invention, the conductive silver paste of the present invention comprises glass frit which is generally used in the art to prepare conductive silver paste for solar cells.
[0064] In one embodiment of the present invention, the conductive silver paste may contain 2-15 wt %, preferably 2.2-10 wt %, more preferably 2.5-8 wt % of glass powder, based on the total weight of the conductive silver paste.
[0065] For example, in one embodiment of the present invention, the glass frit is prepared from a glass frit composition comprising tellurium oxide, lead oxide, optional bismuth oxide, and optional silicon dioxide in amounts commonly used in the art.
[0066] In a preferred embodiment of the present invention, the glass powder composition comprises, based on the total amount of the glass powder composition:
[0067] Tellurium oxide: 10-50 mol%, preferably 15-40 mol%;
[0068] Lead oxide: 10-30 mol%, preferably 15-25 mol%;
[0069] Bismuth oxide: 0-15 mol%, preferably 5-10 mol%;
[0070] Silicon dioxide: 0-30 mol%, preferably 5-25 mol%.
[0071] In a further preferred embodiment of the present invention, the glass powder composition further comprises optional oxides of alkali metals, preferably selected from Li, Na, K, or combinations thereof; optional oxides of alkaline earth metals, preferably selected from Ca, Mg, Sr, or combinations thereof; and optional oxides of metals, preferably selected from Zn, Cu, Mo, W, Ag, V, Cr, Mn, Co, Ni, Nb, Ta, Th, Ge, La, Sb, Ce, Al, or combinations thereof.
[0072] In a further preferred embodiment of the present invention, based on the total amount of the glass powder composition, the glass powder composition comprises:
[0073] Alkali metal oxides or combinations: 0-30 mol%, preferably 15-25 mol%;
[0074] Alkaline earth metal oxides or combinations: 0-10 mol%, preferably 0-5 mol%; and
[0075] Transition metal oxides or combinations thereof: 0-40 mol%, preferably 5-25 mol%.
[0076] Obviously, the sum of the contents of the various components of the glass powder composition is 100 weight %.
[0077] Those skilled in the art will appreciate that the metal oxide in the glass powder composition may be added in the form of a metal salt that can be pyrolyzed to generate the metal oxide, as long as the pyrolysis product thereof does not interfere with the realization of the functions of other components.
[0078] For example, the alkali metal oxide may be added in the form of the alkali metal carbonate, which produces the alkali metal oxide and carbon dioxide during pyrolysis, wherein the carbon dioxide escapes in the form of gas and does not interfere with the performance of the functions of other metal oxides.
[0079] In one embodiment of the present invention, the glass frit is prepared using a method commonly used in the art for preparing glass frit from a glass frit composition.
[0080] For example, the glass powder is prepared by the following method: uniformly mixing the components of the glass powder composition, melting the mixture to obtain glass, preferably quenching the mixture in deionized water, and finally preparing particles with a desired particle size.
[0081] Preferably, the glass powder is prepared by the following method: uniformly mixing the components of the glass powder composition, charging the mixture into a crucible, placing the crucible in a muffle furnace and melting the mixture at a high temperature, then removing the molten glass from the muffle furnace and pouring it into a bucket filled with deionized water for water quenching, and grinding the quenched glass slag with a ball mill to obtain glass powder with a desired particle size D50.
[0082] In one embodiment of the present invention, the glass powder has a particle size D50 of 0.1-5 μm, for example 0.2 μm, 0.5 μm, 0.8 μm, 1 μm, 1.2 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm or 4.5 μm, preferably 1-2 μm.
[0083] In the above method, the temperature of the muffle furnace is high enough to melt the components of the glass powder, and the melting time is long enough to uniformly mix the components.
[0084] More preferably, in the preparation of the glass powder, the temperature of the muffle furnace is 800-1500° C., preferably 900-1200° C., and the melting time of the mixture is 15 minutes to 2 hours, preferably 30 minutes to 1 hour.
[0085] In one embodiment of the present invention, the conductive silver paste of the present invention comprises 2-15 wt %, preferably 2.2-10 wt %, more preferably 2.5-8 wt % of glass powder, based on the total weight of the conductive silver paste.
[0086] In one embodiment of the present invention, the conductive silver paste of the present invention comprises an organic vehicle commonly used in the art, which is a solution, emulsion or dispersant based on one or more solvents, preferably an organic solvent, which ensures that the components of the conductive silver paste are present in a dissolved, emulsified or dispersed form. The preferred organic vehicle is an organic vehicle that provides the best stability of the components in the conductive silver paste and imparts viscosity to the conductive silver paste that allows effective printability.
[0087] In one embodiment, the amount of the organic vehicle may be 2-20 wt %, more preferably 3-15 wt %, most preferably 5-10 wt %, based on the total weight of the conductive silver paste.
[0088] In one embodiment, the organic vehicle comprises an organic solvent, a binder (eg, a polymer, a resin), a surfactant, or an additive, or any combination thereof. For example, in one embodiment, the organic vehicle comprises one or more binders in an organic solvent.
[0089] The binder can be present in an amount of 0.1-10 wt %, preferably 0.1-8 wt %, more preferably 0.5-7 wt %, based on the total weight of the organic vehicle. Preferred binders are those that promote the formation of conductive silver pastes with favorable stability, printability, viscosity and sintering properties. Preferred binders (which generally belong to the category referred to as "resins") are polymeric binders, monomeric binders, and binders that are combinations of polymers and monomers. The polymeric binder can also be a copolymer.
[0090] Preferred polymeric binders include binders carrying functional groups in the polymer backbone, binders carrying functional groups outside the backbone, and binders carrying functional groups inside and outside the backbone. Preferred polymers carrying functional groups in the backbone include, for example, polyesters, substituted polyesters, polycarbonates, substituted polycarbonates, polymers carrying cyclic groups in the backbone, polysaccharides, substituted polysaccharides, polyurethanes, substituted polyurethanes, polyamides, substituted polyamides, phenolic resins, substituted phenolic resins, copolymers of one or more monomers of the above polymers (optionally with other comonomers) or combinations of at least two thereof.
[0091] Preferred polymers carrying cyclic groups in the main chain include, for example, polyvinyl butyral (PVB) and its derivatives and polyterpineol and its derivatives or mixtures thereof. Preferred polysaccharides include, for example, ethyl cellulose, cellulose and its alkyl derivatives, methyl cellulose, hydroxyethyl cellulose, propyl cellulose, hydroxypropyl cellulose, butyl cellulose, its derivatives and mixtures of at least two thereof. Other preferred polymers include, for example, cellulose ester resins, such as cellulose acetate propionate, cellulose acetate butyrate and any combination thereof. Other preferred polymers are those disclosed in U.S. Patent Application Publication No. 2013 / 0180583, which is incorporated herein by reference.
[0092] Preferred polymers carrying functional groups outside the polymer backbone are polymers carrying amide groups, polymers carrying acid and / or ester groups (commonly referred to as acrylic resins) or polymers carrying a combination of the above functional groups or combinations thereof. Preferred polymers carrying amide groups outside the backbone include, for example, polyvinyl pyrrolidone (PVP) and its derivatives. Preferred polymers carrying acid and / or ester groups outside the backbone include, for example, polyacrylic acid and its derivatives, polymethyl methacrylate (PMMA) and its derivatives or mixtures thereof.
[0093] Preferred monomeric binders according to the present invention include, for example, monomeric binders based on ethylene glycol. Preferred monomeric binders based on ethylene glycol are binders having multiple ether groups, multiple ester groups, or binders having one ether group and one ester group, preferably the ether groups are methyl, ethyl, propyl, butyl, pentyl, hexyl and higher alkyl ethers, preferably the ester groups are acetates and their alkyl ether derivatives, preferably ethylene glycol monobutyl ether monoacetate or mixtures thereof.
[0094] Preferred binders in the present invention are, for example, alkyl cellulose (preferably ethyl cellulose), derivatives thereof, and mixtures thereof with other binders from the previous binder list, and the like.
[0095] The amount of the organic solvent may be 40 to 90% by weight, more preferably 35 to 85% by weight, based on the total weight of the organic vehicle.
[0096] Preferred solvents according to the present invention are solvents that allow the formation of silver-aluminum pastes with favorable viscosity, printability, stability and sintering properties. All solvents known in the art and considered suitable in the present invention can be used as solvents in the organic vehicle. According to the present invention, preferred solvents are solvents that allow a preferred high level of printability of the silver-aluminum paste as described above to be achieved. Preferred solvents according to the present invention are solvents that exist in liquid form at standard ambient temperature and pressure (SATP) (298.15K, 100kPa), preferably solvents having a boiling point above about 90°C and a melting point above about -20°C.
[0097] Preferred solvents according to the invention are polar or nonpolar, protic or aprotic, aromatic or nonaromatic. Preferred solvents according to the invention include, for example, monoalcohols, diols, polyalcohols, monoesters, diesters, polyesters, monoethers, diethers, polyethers, solvents comprising at least one or more of these classes of functional groups, optionally comprising other classes of functional groups, preferably cyclic groups, aromatic groups, unsaturated bonds, alcohol groups having one or more O atoms substituted by heteroatoms, ether groups having one or more O atoms substituted by heteroatoms, ester groups having one or more O atoms substituted by heteroatoms, and mixtures of two or more of the above solvents.
[0098] The organic vehicle may further include a surfactant and / or an additive. The amount of the surfactant may be 0-10% by weight, preferably 0-8% by weight, more preferably about 0.01-6% by weight, based on the gross weight of the organic vehicle. Preferred surfactants in the present invention are surfactants that promote the formation of silver-aluminum pastes with favorable stability, printability, viscosity and sintering properties. All surfactants known in the art and considered to be applicable in the present invention may be used as surfactants in the organic vehicle. Preferred surfactants are single-chain, double-chain or poly-chain. Preferred surfactants according to the present invention may have nonionic, anionic, cationic, amphoteric or zwitterionic heads. Preferred surfactants are polymeric and monomeric or mixtures thereof.
[0099] Preferred additives in the organic vehicle are those additives that are different from the above-mentioned vehicle components and promote the favorable properties of the conductive silver paste (such as favorable viscosity and adhesion to the underlying substrate). Additives known in the art and considered suitable in the present invention can be used as additives in the organic vehicle. Preferred additives are thixotropic agents, viscosity regulators, stabilizers, inorganic additives, thickeners, emulsifiers, dispersants, slip agents or pH regulators and any combination thereof. Preferred thixotropic agents herein are carboxylic acid derivatives, preferably fatty acid derivatives or combinations thereof. Preferred fatty acid derivatives are C9H 19 COOH (decanoic acid), C 11 H 23 COOH (lauric acid), C 13 H 27 COOH (myristic acid), C 15 H 31 COOH (palmitic acid), C 17 H 35 COOH(stearic acid), C 18 H 34 O2(oleic acid), C 18 H 32 O2 (linoleic acid) or a combination thereof. In this context, castor oil and hydrogenated castor oil are preferred.
[0100] In one embodiment of the present invention, the conductive silver paste of the present invention optionally comprises a conductive silver paste additive commonly used in the art.
[0101] Preferred conductive silver paste additives are components added to the conductive silver paste in addition to the ingredients that have been explicitly mentioned, which are used to promote higher performance of the conductive silver paste, the electrode made therefrom or the resulting solar cell. All conductive silver paste additives known in the art and considered suitable in the present invention can be used as conductive silver paste additives in the conductive silver paste. Preferred conductive silver paste additives are thixotropic agents, viscosity regulators, emulsifiers, stabilizers or pH regulators, inorganic additives (such as silicon powder), thickeners and dispersants or a combination of at least two thereof, and inorganic additives are most preferred. Preferred inorganic additives are Mg, Ni, Te, W, Zn, Mg, Gd, Ce, Zr, Ti, Mn, Sn, Ru, Co, Fe, Cu and Cr or a combination of at least two thereof, preferably Zn, Sb, Mn, Ni, W, Te and Ru or a combination of at least two thereof, their oxides, compounds that can produce the metal oxide when fired, or mixtures of at least two of the above metals, mixtures of at least two of the above oxides, mixtures of at least two of the above compounds that can produce the metal oxide when fired, or mixtures of two or more of any of the above materials. The amount of the inorganic additive may be 0-1 wt % (eg, 0.1 wt %, 0.5 wt % or 0.8 wt %) based on the total weight of the conductive silver paste.
[0102] In one embodiment of the present invention, the conductive silver paste of the present invention comprises the acetic acid resistant additive of the present invention.
[0103] In one embodiment of the present invention, the conductive silver paste may contain 2-15 wt %, preferably 2.5-8 wt %, and more preferably 0.1-6 wt % of glass powder and acetic acid resistant additives, based on the total weight of the conductive silver paste, wherein the weight ratio of the glass powder to the acetic acid resistant additive is 1:1-20:1, preferably 5:1-15:1, and more preferably 8:1-12:1.
[0104] In one embodiment of the present invention, to form a conductive silver paste, glass powder, silver powder, organic vehicle and optional conductive silver paste additives, and the acetic acid resistant additive of the present invention can be combined using any method known in the art for preparing a paste. The preparation method is not critical as long as it produces a homogeneously dispersed paste. The components can be mixed, such as with a mixer, and then passed through a three-roll mill, for example, to make a dispersed uniform paste.
[0105] In one embodiment of the present invention, the conductive silver paste has a particle size D50 of 0.1-5 μm, preferably 1-2 μm, for example 0.2 μm, 0.5 μm, 0.8 μm, 1 μm, 1.2 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm or 4.5 μm.
[0106] Those skilled in the art should be aware that the conductive silver paste of the present invention can also be obtained using other embodiments.
[0107] For example, in another embodiment of the present invention, in order to form a conductive silver paste, the glass powder composition corresponding to the glass powder of the present invention and the components of the anti-acetic acid additive of the present invention can be first combined, and then the glass powder containing the anti-acetic acid additive of the present invention is formed according to the above-mentioned method for preparing glass powder, and the conductive silver paste of the present invention is prepared using the glass powder instead of the combination of the glass powder and the anti-acetic acid additive of the present invention according to the above-mentioned method for preparing conductive silver paste.
[0108] Solar Cells
[0109] The present invention further relates to a solar cell comprising a substrate and an electrode formed by sintering the conductive silver paste of the present invention and bonded to the substrate.
[0110] A preferred solar cell according to the present invention is one that has a high efficiency in terms of the ratio of the total energy of incident light converted to electrical energy output. Lightweight and durable solar cells are also preferred. A solar cell comprises at least: (i) a front electrode, (ii) a front doped layer, (iii) a pn junction boundary, (iv) a back doped layer and (v) a back electrode and (vi) a passivation layer. The solar cell may also include additional layers for chemical / mechanical protection.
[0111] The solar cell substrate of the present invention may be a substrate for solar cells known to those skilled in the art.
[0112] The solar cell of the present invention has an electrode formed by sintering the conductive silver paste of the present invention and bonded to the substrate.
[0113] In one embodiment of the present invention, the homogenized conductive silver paste containing the acetic acid resistant additive can be applied to the substrate by any method known in the art and considered suitable in the present invention. Examples of the method include, but are not limited to, dipping, impregnation, pouring, dripping, injection, spraying, blade coating, shower coating, brushing or printing or a combination of at least two thereof. Preferably, the printing technique is inkjet printing, screen printing, flexographic printing, offset printing, relief printing or stencil printing or a combination of at least two thereof. According to the present invention, it is preferred that the homogenized conductive silver paste containing the acetic acid resistant additive is applied by printing, preferably by screen printing.
[0114] Firing is required to sinter the printed electrodes to form a solid conductor. Firing is well known in the art and may be achieved in any manner deemed appropriate in the present invention. It is preferred that firing is performed above the Tg of the glass frit material.
[0115] Outside the area occupied by the electrodes, the substrate of the present invention, preferably a silicon wafer, has an area where light can be efficiently absorbed to generate electron-hole pairs and efficiently separate holes and electrons across a boundary, preferably a pn junction boundary.
[0116] The pn junction boundary is located where the front doped layer of the wafer meets the back doped layer. In an n-type solar cell, the back doped layer is doped with an n-type dopant and the front doped layer is doped with a p-type dopant. In a p-type solar cell, the back doped layer is doped with a p-type dopant and the front doped layer is doped with an n-type dopant. According to a preferred embodiment of the present invention, a wafer having a pn junction boundary is prepared by first providing a doped silicon substrate and then applying a doped layer of the opposite type to one face of the substrate.
[0117] The above-mentioned dopants are preferably dopants that form pn junction boundaries by introducing electrons or holes into the band structure when added to the silicon wafer. According to the present invention, it is preferred to specifically select the types and concentrations of these dopants to adjust the band structure profile of the pn junction and set the light absorptivity and conductivity profile as required. The preferred p-type dopant according to the present invention is a dopant that adds holes to the band structure of the silicon wafer. All dopants known in the art and considered suitable in the present invention can be used as p-type dopants. The preferred p-type dopant according to the present invention is a trivalent element, especially a trivalent element of Group 13 in the periodic table. The preferred Group 13 elements in the periodic table herein include, but are not limited to, boron, aluminum, gallium, indium, thallium or a combination of at least two thereof, wherein boron is particularly preferred.
[0118] Preferred n-type dopants according to the present invention are dopants that add electrons to the band structure of the silicon wafer. All dopants known in the art and considered suitable in the present invention can be used as n-type dopants. Preferred n-type dopants according to the present invention are elements of the fifth group of the periodic table. Preferred elements of the fifth group of the periodic table herein include nitrogen, phosphorus, arsenic, antimony, bismuth or a combination of at least two thereof, wherein phosphorus is particularly preferred.
[0119] According to the present invention, an antireflection layer may be applied as an outer layer before the electrode is applied to the front side of the solar cell. A preferred antireflection layer according to the present invention is an antireflection layer that reduces the proportion of incident light reflected by the front side and increases the proportion of incident light that will be absorbed by the wafer across the front side. An antireflection layer that produces a favorable absorptivity / reflectivity ratio is susceptible to etching with a conductive silver paste, is further resistant to the temperature required for firing the conductive silver paste, and does not promote greater recombination of electrons and holes near the electrode interface. All antireflection layers known in the art and considered suitable for use in the present invention may be used. A preferred antireflection layer according to the present invention is silicon nitride, silicon dioxide, aluminum oxide, titanium oxide, or a mixture of at least two thereof and / or a combination of at least two layers thereof. According to a preferred embodiment, the antireflection layer is silicon nitride, i.e., Si x N y , especially wherein a silicon wafer is employed, wherein x is approximately 2-4 and y is approximately 3-5.
[0120] According to the present invention, one or more passivation layers can be applied to the substrate, preferably the front side and / or back side of the silicon wafer as the outer layer. The passivation layer can be applied before forming the front electrode or before applying the anti-reflection layer (if one of them exists). Preferably, the passivation layer is a passivation layer that reduces the electron / hole recombination rate near the electrode interface. Any passivation layer known in the art and considered to be applicable in the present invention can be used. According to the present invention, the passivation layer can be silicon nitride, aluminum oxide silicon dioxide and titanium dioxide. According to the most preferred embodiment, aluminum oxide is used. Preferably, the passivation layer has a thickness of 0.1nm to 2μm, more preferably 1nm to 1μm, and most preferably 1nm to 200nm.
[0121] Besides the above-mentioned layers which directly contribute to the main functions of the solar cell, further layers can be added according to the invention for mechanical and chemical protection.
[0122] The battery can be encapsulated to provide chemical protection. Encapsulation is well known in the art and any encapsulation suitable for the present invention can be used. According to a preferred embodiment, a transparent polymer (commonly referred to as a transparent thermoplastic resin) is used as an encapsulation material, provided that such an encapsulation exists. Preferred transparent polymers herein are silicone rubber and polyethylene vinyl acetate (EVA).
[0123] A transparent glass sheet may also be added to the front side of the solar cell to provide mechanical protection thereto. Transparent glass sheets are well known in the art, and any transparent glass sheet suitable for use in the present invention may be employed.
[0124] A backside protection material may be added to the back side of the solar cell to provide mechanical protection. Backside protection materials are well known in the art and any backside protection material deemed suitable in the present invention may be used. A preferred backside protection material according to the present invention is a backside protection material having good mechanical properties and weatherability. A preferred backside protection material according to the present invention is polyethylene terephthalate with a polyvinyl fluoride layer. It is preferred according to the present invention that the backside protection material is present below the encapsulation layer (in the case where a backside protection layer and encapsulation are present).
[0125] Frame materials may be added to the outside of the solar cell to impart mechanical support. Frame materials are well known in the art and any frame material deemed suitable for use in the present invention may be employed. A preferred frame structure according to the present invention is aluminum.
[0126] In one embodiment of the present invention, the acetic acid-resistant additive of the present invention is added to the conductive silver paste that has been prepared, the conductive silver paste containing the acetic acid-resistant additive is homogenized, and then the homogenized conductive silver paste containing the acetic acid-resistant additive is applied to a substrate, such as a semiconductor substrate (such as a silicon wafer), to form a printed electrode.
[0127] In one embodiment of the present invention, 2-15 wt %, preferably 2.2-10 wt %, more preferably 2.5-8 wt % of the anti-acetic acid additive based on the total amount of the conductive silver paste without the anti-acetic acid additive is added to the conductive silver paste without the anti-acetic acid additive.
[0128] In one embodiment of the present invention, the conductive silver paste containing the acetic acid resistant additive can be homogenized by any method known in the art and considered suitable in the present invention, as long as it produces a uniformly dispersed slurry. For example, a mixer can be used for mixing, and then a three-roll mill can be used to make a dispersed uniform slurry.
[0129] The present invention reduces the acetic acid attenuation of solar cell sheets by adding an acetic acid resistant additive to the conductive silver paste without significantly changing the formula, preparation method and conditions of the conductive silver paste, while maintaining the initial efficiency of the solar cell sheets unchanged.
[0130] Example
[0131] The following examples show the acetic acid resistant additive of the present invention, the conductive silver paste containing the acetic acid resistant additive, the homogenized conductive silver paste containing the acetic acid resistant additive, and the preparation method and product performance of the solar cell prepared by the homogenized conductive silver paste containing the acetic acid resistant additive.
[0132] raw material
[0133] Tellurium oxide, boron oxide, lead oxide, bismuth oxide, and niobium oxide are 4N chemical reagents.
[0134] The silver powder is spherical silver powder with a D50 of 1.5 μm.
[0135] The fatty acid and fatty acid amide were dodecyl hydroxystearic acid and Disparlon 6500 purchased from Kusumoto Chemicals Co., Ltd., Japan, respectively.
[0136] The silicon wafer is a P-type silicon wafer with a size of 182mm and a passivation layer.
[0137] Potassium chloride and glacial acetic acid were analytically pure chemical reagents.
[0138] The glass powder composition is as follows:
[0139] Bismuth oxide: 10 parts by weight;
[0140] Copper oxide: 1 part by weight;
[0141] Potassium oxide: 1 part by weight;
[0142] Tellurium oxide: 45 parts by weight;
[0143] Lead oxide: 20 parts by weight;
[0144] Zinc oxide: 5 parts by weight;
[0145] Lithium carbonate: 10 parts by weight;
[0146] Silicon dioxide: 3 parts by weight;
[0147] Tungsten oxide: 5 parts by weight.
[0148] The organic carrier is composed as follows:
[0149] Diethylene glycol butyl ether acetate (organic solvent): 5.6 parts by weight;
[0150] Cellulose acetate butyrate (resin): 0.6 parts by weight;
[0151] Oleic acid (organic dispersant): 0.6 parts by weight;
[0152] Hydrogenated castor oil (thixotropic agent): 0.6 parts by weight;
[0153] Alkyl-modified silicone oil (lubricant): 0.6 parts by weight.
[0154] Test Method
[0155] IV Experiment
[0156] The cells were subjected to IV tests using a commercial IV tester "cetisPV-Celltest4-BF" from Halm Elektronik GmbH to obtain Eff (cell conversion efficiency).
[0157] Acetic acid immersion test
[0158] Add 115 g of potassium chloride to a beaker containing 194 g of deionized water, then add 6 ml of glacial acetic acid and continue stirring with a glass rod for more than 2 minutes;
[0159] Pour the prepared solution into a polypropylene box;
[0160] Place the cells to be tested in the holder with a certain gap, and put the holder with cells into the polypropylene box, making sure there is no direct contact between the cells and the solution;
[0161] The polypropylene box was sealed and placed in an oven at 85° C. for 15 hours. The battery cell was taken out and dried to obtain the battery cell after the acetic acid immersion test.
[0162] Preparation of samples of acetic acid resistant additives
[0163] Weigh the components of the acetic acid resistant additive according to the ratio shown in Table 1 and combine them;
[0164] It was loaded into an alumina crucible, placed in a muffle furnace and kept at 1100°C for 60 minutes;
[0165] The alumina crucible containing the molten glass is then removed from the muffle furnace, and the molten glass is poured into a bucket containing deionized water for water quenching;
[0166] The water-quenched glass slag was ground by a ball mill until D50 was about 1.5 μm, thereby obtaining acetic acid resistant additive samples ad.
[0167] Table 1. Composition of acetic acid resistant additives (weight %)
[0168]
[0169] Preparation of conductive silver paste samples
[0170] 88 wt % of silver powder, 2 wt % of glass powder, 1 wt % of fatty acid amide, 1 wt % of fatty acid, and 8 wt % of an organic vehicle were mixed, mixed with a planetary mixer, and then mixed with a three-roll mill, thereby preparing a conductive silver paste sample 1;
[0171] The acetic acid resistant additive samples ad were added to the conductive silver paste sample 1 at a ratio of 0.2 wt %, and mixed using a three-roll mill, thereby preparing conductive silver paste samples 2-5.
[0172] The amounts of the above components are all based on the total weight of the conductive silver paste.
[0173] Preparation of battery cells
[0174] The conductive silver paste of the conductive silver paste sample 1-5 was printed onto a silicon wafer by screen printing, and then sintered in a chain sintering furnace at a peak temperature of 750-800° C. for 30 minutes, thereby preparing the battery cell sample 1-5.
[0175] Battery performance test
[0176] Before and after the acetic acid immersion test, the same cell was used to conduct an IV test to determine the conversion efficiency of the cell before and after the acetic acid immersion test;
[0177] Acetate decay is defined as the percentage decrease in transformation efficiency:
[0178] Acetic acid attenuation = (battery conversion efficiency before acetic acid immersion test - battery conversion efficiency after acetic acid immersion test) / battery conversion efficiency before acetic acid immersion test × 100%
[0179] The IV test results and acetic acid attenuation after the acetic acid immersion test are listed in Table 2.
[0180] Table 2. IV test results and acetic acid attenuation before and after acetic acid immersion
[0181]
[0182] Conductive silver paste sample 1 and solar cell sample 1 correspond to the conductive silver paste conventionally used in the art and the solar cell prepared therefrom, and conductive silver paste samples 2-5 correspond to the conductive silver paste containing the acetic acid-resistant additive of acetic acid-resistant additive samples ad and the solar cell prepared therefrom.
[0183] It can be seen from Table 2 that compared with the solar cell 1 prepared with the conductive silver paste without the acetic acid resistant additive samples ad, the initial efficiency of the solar cells 2-5 prepared with the conductive silver paste containing the acetic acid resistant additive samples ad remains basically unchanged.
[0184] It can also be seen from Table 2 that, compared with the solar cell 1 prepared with the conductive silver paste without the acetic acid resistant additive samples ad, the acetic acid attenuation of the solar cells 2-5 prepared with the conductive silver paste containing the acetic acid resistant additive samples ad was reduced by more than half.
[0185] It can be further seen from Table 2 that, compared with the solar cells prepared without using the acetic acid-resistant additives of the acetic acid-resistant additive samples ad, the solar cells prepared using the conductive silver paste containing the acetic acid-resistant additive sample a after the acetic acid immersion experiment achieved the highest cell conversion efficiency on the one hand, and the lowest acetic acid attenuation on the other hand.
Claims
1. An acetic acid resistant additive, wherein based on the total weight of the acetic acid resistant additive, the acetic acid resistant additive comprises: Te2O3: 20-80 wt%, preferably 40-70 wt%, more preferably 45-60 wt%, most preferably 45-55 wt%; B2O3: 0-10 wt%, preferably 0-8 wt%, more preferably 2-6 wt%, most preferably 3-5 wt%; PbO: 1-70 wt %, preferably 5-60 wt %, more preferably 20-50 wt %, most preferably 25-50 wt %; Bi2O3: 5-50 wt%, preferably 10-40 wt%, more preferably 10-30 wt%, most preferably 10-25 wt%; and Nb2O3: 0-20 wt%, preferably 0-10 wt%, more preferably 2-6 wt%, most preferably 3-5 wt%; The total amount of each component is 100% by weight.
2. The acetic acid resistant additive according to claim 1, which has a particle size D50 of 0.1-5 μm, preferably 1-2 μm.
3. The acetic acid resistant additive of claim 1, having a 2 / g, preferably 1.5-3.5m 2 / g specific surface area.
4. A conductive silver paste comprising silver powder, glass powder, an organic carrier and an optional conductive silver paste additive, and the acetic acid-resistant additive according to any one of claims 1 to 3.
5. The conductive silver paste of claim 4, wherein based on the total weight of the conductive silver paste, it comprises: silver powder: 80-94 wt%, preferably 79-93 wt%, more preferably 82-92 wt%; Glass powder and acetic acid resistant additive: 2-15% by weight, preferably 2.5-8% by weight, more preferably 0.1-6% by weight, wherein the weight ratio of glass powder to acetic acid resistant additive is 1:1-20:1, preferably 5:1-15:1, more preferably 8:1-12:1; Organic carrier: 2-20% by weight, preferably 3-15% by weight, more preferably 5-10% by weight; wherein the total amount of each component is 100% by weight.
6. The conductive silver paste of claim 4 or 5, wherein based on the total weight of each component of the glass powder, the glass powder comprises: Tellurium oxide: 10-50 mol%, preferably 15-40 mol%; Lead oxide: 10-30 mol%, preferably 15-25 mol%; Bismuth oxide: 0-15 mol%, preferably 5-10 mol%; Silicon dioxide: 0-30 mol%, preferably 5-25 mol%; Preferably selected from the oxides or combinations of alkali metals Li, Na, K: 0-30 mol%, preferably 15-25 mol%; Preferably selected from the oxides or combinations of alkaline earth metals Ca, Mg, Sr: 0-10 mol%, preferably 0-5 mol%; and Preferably selected from oxides of transition metals Zn, Cu, Mo, W, Ag, V, Cr, Mn, Co, Ni, Nb, Ta, Th, Ge, La, Sb, Ce, Al or combinations thereof: 0-40 mol%, preferably 5-25 mol%; The sum of the contents of each component is 100 mol%.
7. A solar cell comprising an electrode obtained from the conductive silver paste according to any one of claims 4 to 6.
8. The solar cell according to claim 7, wherein the electrode is located on a silicon wafer with a passivation layer, preferably a P-type silicon wafer.
9. Use of the acetic acid resistant additive according to any one of claims 1 to 3, for reducing acetic acid attenuation of solar cell sheets while maintaining the initial efficiency of the solar cell sheets, wherein the acetic acid resistant additive is added to a conductive silver paste for preparing solar cell sheets.
10. A method for reducing acetic acid attenuation of solar cell sheets while maintaining the initial efficiency of the solar cell sheets, wherein the acetic acid-resistant additive according to any one of claims 1 to 3 is added to the conductive silver paste used to prepare the solar cell sheets before sintering the conductive silver paste.
Citation Information
Patent Citations
Conductive paste for fine-line high-aspect-ratio screen printing in the manufacture of semiconductor devices
US20130180583A1